Application of Transportation Models for Biopharmaceutical Crops Harvest Optimization - Shelly Sholatan Kamilah; Hendra Sumantri (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Transportation models are typically used to optimize shipping costs for products, however, their application in agricultural harvest planning remains limited. The purpose of this study is to explore the use of transportation models for optimizing biopharmaceutical crop harvest production. The research method is a quantitative optimization approach by transforming harvest production and land allocation data into a transportation model matrix. The matrix of the transportation model for the harvest of biopharmaceutical crops is adjusted to address the existing problems. In this model, sub-districts were treated as sources, crop types as destinations, and average harvest yield per square meter as the optimization parameter. The model that has been formed is then simulated and solved using POM-QM software with Vogel's Approximation Method (VAM). The model solution shows that the harvest of all biopharmaceutical crops is 4,187,642 Kg. This means that the simulation results of the transportation model are 136,697 Kg (3.37%) more than the data in 2023. These findings indicate that the transportation model can effectively support harvest production planning.